Cholinesterase and Tyrosinase Inhibitory Potential and Antioxidant Capacity of Lysimachia verticillaris L. and Isolation of the Major Compounds - GÖREN, AHMET CEYHAN; ÖZGEN, UFUK; ŞENER, SILA ÖZLEM; Smejkal, Karel; Vaclavik, Jiri; ŞENOL DENİZ, FATMA SEZER; ERDOĞAN ORHAN, İLKAY; Svajdlenka, Emil; GÖREN, AHMET CEYHAN; Zemlicka, Milan (My University, 2020)
Objectives: The scope of the present study was to specify the therapeutic potential for neurodegenerative diseases through evaluating cholinesterase and tyrosinase (TYR) inhibitory and antioxidant activity of Lysimachia verticillaris (LV), and to isolate the major compounds considering the most active fraction.